Mechanobiology of tissue differentiation during osteochondral defect repair - Kelly, Daniel John (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2004)
Differentiation can be thought of as a process by which cells and tissues undergo a change in phenotype toward a more specialized form or function. It is the contention of this thesis that tissue differentiation is in some way regulated by the mechanical environment of the cells within the tissue. A theoretical model was developed which relates the dispersal, proliferation, and death of cells, and their subsequent differentiation, to their mechanical environment. In an attempt to confirm this mechano-regulation hypothesis, an algorithm based on the theoretical model was developed and used to simulate tissue differentiation during spontaneous osteochondral defect repair, where the mechanical environment within the defect was determined using finite element modelling. The influence of a number of physical factors, such as defect size and loading, were studied by altering these parameters in the finite element model. Furthermore, the influence of implanting a scaffold or engineered cartilage tissue on osteochondral defect repair was examined, where the mechanical properties of tissue engineered cartilage was determined experimentally.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin